fMRI evidence of a hot-cold empathy gap in hypothetical and real aversive choices - Kang, Min J.; Camerer, Colin F. (Frontiers in Neuroscience, 2013)
Hypothetical bias is the common finding that hypothetical monetary values for “goods” are higher than real values. We extend this research to the domain of “bads” such as consumer and household choices made to avoid aversive outcomes (e.g., insurance). Previous evidence of hot-cold empathy gaps suggest food disgust is likely to be strongly underestimated in hypothetical (cold) choice. Depending on relative underestimation of food disgust and pain of spending, the hypothetical bias for aversive bads can go in the typical direction for goods, disappear, or reverse in sign. We find that the bias is reversed in sign—subjects pay more to avoid bads when choice is real. fMRI shows that real choice more strongly activates striatum and medial prefrontal cortex (reward regions) and shows distinct activity in insula and amygdala (disgust and fear regions). The neural findings suggest ways to exogeneously manipulate or record brain activity in order to create better forecasts of actual consumer choice.